Fitness Leader's Handbook / Second Edition - Franks B. Don; Howley Edward T (Human Kinetics, 1989)
This book is an ideal reference for anyone charged with the task of leading a fitness class. Preface, Acknowledgements, Bases for Fitness Programs, Fitness, Fitness Program, Who Should Be in a Fitness Program?, Health Status, Screening, Fitness Components, Desired Weight, Health Nutrition Plans, Desired Aerobic Fitness, Muscular Strength and Endurance, Flexibility, Preventing Low-Back Problems, Coping with Stress, The Fitness Program, Recommendations for Physical Activity, Fitness Activities, Measuring Energy Expenditure, Behavior Modification, Scientific Foundations, Basic Exercise Science, Measurement and Evaluation, Safe and Effective Programs, Preventing and Treating Injuries, Special Personal Conditions, Environmental Problems, Program Organization, Human Relations, Appendix: Recommended Dietary Allowances and Intakes, Definitions, Bibliography, Credits, Index.